Benefits to Plant Health and Productivity From Enhancing Plant Microbial Symbionts - Harman, Gary; Khadka, Ram; Doni, Febri; Uphoff, Norman (Frontiers in Plant Science, 2021)
Abstract Plants exist in close association with uncountable numbers of microorganisms around, on, and within them. Some of these endophytically colonize plant roots. The colonization of roots with certain symbiotic strains of plant-associated bacteria and fungi results in these plants performing better than plants whose roots are colonized with only the wild populations of microbes. We consider here crop plants whose roots are inhabited by introduced organisms, referring to them as Enhanced Plant Holobionts (EPHs). EPHs frequently exhibit resistance to specific plant diseases and pests (biotic stresses); resistance to abiotic stresses such as drought, cold, salinity, and flooding; enhanced nutrient acquisition and nutrient use efficiency; increased photosynthetic capability; and enhanced ability to maintain efficient internal cellular functioning. The microbes described here generate effects in part through their production of Symbiont-Associated Molecular Patterns (SAMPs) that interact with receptors in plant cell membranes. Such interaction results in the transduction of systemic signals that cause plant-wide changes in the plants’ gene expression and physiology. EPH effects arise not only from plant-microbe interactions, but also from microbe-microbe interactions like competition, mycoparasitism, and antibiotic production. When root and shoot growth are enhanced as a consequence of these root endophytes, this increases the yield from EPH plants. An additional benefit from growing larger root systems and having greater photosynthetic capability is greater sequestration of atmospheric CO2. This is transferred to roots where sequestered C, through exudation or root decomposition, becomes part of the total soil carbon, which reduces global warming potential in the atmosphere. Forming EPHs requires selection and introduction of appropriate strains of microorganisms, with EPH performance affected also by the delivery and management practices.